Respuesta :

Step-by-step explanation:

[tex]9\left(x-6\right)+41=75\\ x=\frac{88}{9}[/tex]

Step 1: Subtract 41 from both sides

[tex]9\left(x-6\right)+41-41=75-41[/tex]

[tex]9\left(x-6\right)=34[/tex]

Step 2: Divide both sides by 9

[tex]\frac{9\left(x-6\right)}{9}=\frac{34}{9}[/tex]

[tex]x-6=\frac{34}{9}[/tex]

Step 3: Add 6 to both sides

[tex]x-6+6=\frac{34}{9}+6[/tex]

[tex]x=\frac{88}{9}[/tex]

Ver imagen Аноним

Answer:

Reason 1 ) Subtraction Property of Equality

Reason 2 ) Substitution Property of Equality

Statement 4 ) 9x = 88

Reason 4 )  Addition Property of Equality

Reason 5 )  Division Property of Equality